The international bibliography of rice research : (International Rice Research Institute, 1981)
This IRRI Rice Research Bibliography Supplement contains references published in 1979 plus those published from 1971 to 1978 which were not included in previous supplements. Additional lists of translations available in the IRRI library and serial titles added to the 1979 supplement are included